KETERTARIKAN WALANG SANGIT (Leptocorisa oratorius F.) TERHADAP BEBERAPA BAHAN ORGANIK YANG MEMBUSUK - ., Solikhin (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Attractiveness of Rice Bug (Leptocorisa oratorius F.) to Several Faunal Decaying Materials. An experiment was conducted in Yogyakarta from October 1996 to September 1997 to know (1) the attractiveness of adult male versus female rice stink bug in to decaying crab, (2) the attractiveness of the rice stink bug from the result of point-1 to five decaying materials, and (3) the volatile compounds emitted by each decaying material. For the first objective, 50 rice stink bugs (sex ratio 1:1) were released into a preference test cage for one hour. Data was then analyzed with X2 at 1 and 5%. For the second objective, five replicates of five different treatments were arranged in randomized completely block design. As many as 125 rice stink bugs were released into the central part of the cage consisting of five equal parts of attractants for one hour. Data of rice stink bug from each part was analyzed with Anova continued with Duncan's Test at 1 and 5%.. Volatile compounds emitted by each material were captured based on the method of Gamliel and Stapleton (1993) then identified with gas chromatography mass spectrophotometry (GC-MS) and (or) capillary gas chromatography. The results were that: (1) adult male rice bug was significantly more attracted to that of female in response to sixth-day-decaying-crab, (2) adult male rice bug was most attracted to sixth-day-decaying cow blood compared to four others, and (3) volatile compounds emitted by those five materials were carbon dioxide, methanol, ethanol, aceton, dimethyl sulphide, dimethyl disulphide, ammonia, acetic acid, and an unidentified compound.